MicroRNAs Associated With Colon Cancer: New Potential Prognostic Markers and Targets for Therapy - Zhu, Junfeng; Xu, Ying; Liu, Shanshan; Qiao, Li; Sun, Jianqiang; Zhao, Qi (Frontiers in Bioengineering and Biotechnology, 2020)
MicroRNAs (miRNAs), which is a kind of non-coding RNAs (ncRNAs) that regulates the expression of target genes, play roles in the occurrence and development of cancers. Colon cancer (COAD) is the second cause of cancer death for mortality. However, the prognostic value of miRNA in COAD are still confusing. In this study, we obtain miRNAs and messenger RNAs (mRNAs) expression profiles of COAD from the Cancer Genome Atlas (TCGA) database. After preliminary data screening and preprocessing, the expression data of 894 miRNAs and 17019 mRNAs are acquired. Then, comparing to the normal samples, 39 upregulated miRNAs and 54 downregulated miRNAs are identified by differential expression analysis. Furthermore, we also obtain 1487 upregulated mRNAs and 2847 downregulated mRNAs. We confirm nine key miRNAs related to survival rate of COAD patients. Moreover, we get 461 common genes both in target genes of the nine key miRNA and differential expressed mRNA by using the predictive analysis tools and a Venn diagram. Through analyzing the protein-protein interaction (PPI) network of 461 common genes and survival analysis, five hub genes are observed as promising biomarkers for COAD prognosis. It is worth mentioning that there is no report showing that PGR and KCNB1 related to COAD. Taken together, we conduct a unique correlation analysis of miRNA-mRNA in COAD patients, and confirmed nine key miRNAs and five hub genes that may be promising prognostic biomarkers for COAD patients. We expect these key miRNAs and hub genes will provide a new way for the study of COAD.